2017
DOI: 10.1016/s1473-3099(16)30523-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a killed oral cholera vaccine (Shanchol) in pregnant women in Malawi: an observational cohort study

Abstract: SummaryBackgroundPregnancy increases the risk of harmful effects from cholera for both mothers and their fetuses. A killed oral cholera vaccine, Shanchol (Shantha Biotechnics, Hydrabad, India), can protect against the disease for up to 5 years. However, cholera vaccination campaigns have often excluded pregnant women because of insufficient safety data for use during pregnancy. We did an observational cohort study to assess the safety of Shanchol during pregnancy.MethodsThis observational cohort study was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…42 The Haiti study, conducted with 263 women with cholera-like illness, also suggested that severe maternal dehydration (risk ratio = 9.4; 95% CI: 2.5-35.3) and severe vomiting (5.1; 95% CI: 1.1-23.8) were risk factors for fetal death. 43,44 These data imply that an OCV should not be counter-indicated during pregnancy, and studies conducted in Guinea, 45 Zanzibar, 46 Malawi, 47 and Bangladesh 48 have not observed statistically significant adverse outcomes to fetus, newborn, or mother from OCV exposure. Given the risk to the fetus from maternal cholera and the excellent vaccine safety record, there is no scientific basis to withhold OCVs from pregnant women.…”
Section: Operational Enhancements To Ocv Usementioning
confidence: 92%
“…42 The Haiti study, conducted with 263 women with cholera-like illness, also suggested that severe maternal dehydration (risk ratio = 9.4; 95% CI: 2.5-35.3) and severe vomiting (5.1; 95% CI: 1.1-23.8) were risk factors for fetal death. 43,44 These data imply that an OCV should not be counter-indicated during pregnancy, and studies conducted in Guinea, 45 Zanzibar, 46 Malawi, 47 and Bangladesh 48 have not observed statistically significant adverse outcomes to fetus, newborn, or mother from OCV exposure. Given the risk to the fetus from maternal cholera and the excellent vaccine safety record, there is no scientific basis to withhold OCVs from pregnant women.…”
Section: Operational Enhancements To Ocv Usementioning
confidence: 92%
“…On the basis of our current understanding of the vaccine and evidence from different studies, pregnant women should not be excluded from oral cholera vaccines during vaccination campaigns. 15,17,18 Disclosure of potential conflicts of interest No potential conflicts of interest were disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal exposure to the OCV conferred no significantly increased risk of pregnancy loss, neonatal mortality, or malformation. 17 An ongoing evaluation is being performed in a randomized controlled trial of Shanchol in over 205,000 individuals in which women who inadvertently received the OCV is being analyzed for pregnancy outcomes in a prospective cohort design.…”
Section: Safety Of Shanchol During Pregnancy In Malawimentioning
confidence: 99%
“…Finally, five studies remained which met our criteria. 6,9,10,15,16 Information on the study characteristics is presented in Table 1 and Table S2. Studies were performed between 2009 and 2015 and published between 2012 and 2019.…”
Section: Literature Search and Characteristics Of Studymentioning
confidence: 99%
“…8 Indeed, the nature of the vaccines, consisting of killed whole cells of Vibrio cholerae incapable of replicating in the gastrointestinal tract, suggests they are likely safe. Studies of the inadvertent vaccination of women who were unaware of their pregnancy status, 6,9 as well as more recent studies of vaccination campaigns where pregnant women were intentionally included, [10][11][12] are now available. Given these emerging clinical studies and the importance of continual evaluation of the safety profiles of pharmacological agents administered during pregnancy, we have conducted the first meta-analysis of pregnancy outcomes following administration of oral cholera vaccines during mass-vaccination campaigns.…”
Section: Introductionmentioning
confidence: 99%